Model Interaksi Santri Pondok Pesantren Ishlahiyyatul Asroriyyah Ringinagung Kediri - Ahmad Fauzi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Creating a conducive social climate, communication between individuals is certainly indispensable as a means of understanding between one person and another personally. Students at Pondok Pesantren Ishlahiyyatul Asroriyyah Ringinagung Kediri are those who live and study at Pondok Pesantren Ishlahiyyatul Asroriyyah with the background of different families, some are from farmers families, teachers, indigenous peoples to migrants from outside Kediri district. Learning atmosphere is also not different from most schools, but certainly, the number of students who study in the boarding school certainly always appear some new problems. This is due to the dynamics of the social life of the students. Knowing further the process as well as the forms of social interaction students of the Pesantren Ishlahiyyatul Asroriyyah, the authors get the following information: Associative interaction models, accommodation, and dissociative interaction models.